2017
DOI: 10.4236/aim.2017.73014
|View full text |Cite
|
Sign up to set email alerts
|

Modified Green Tea Polyphenols, EGCG-S and LTP, Inhibit Endospore in Three <i>Bacillus</i> spp.

Abstract: Endospores have the ability to withstand extreme temperature, desiccation, ultraviolet radiation and chemicals which make them a threat to the food and healthcare industry. Green tea polyphenols (GTP), contain anti-microbial and anti-spore properties but not stable. In this study, two modified lipophilic green tea polyphenols, epigallocatechin-3-gallate-sterate (EGCG-S) and crude lipophilic green tea polyphenols (LTP), were used to compare their anti-spore effect with EGCG and crude GTP. Purified endospores fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
12
0
3
Order By: Relevance
“…Thus, in this study, we have used a patented (US8076484B2) esterified derivative of EGCG, EGCG-Stearate (EGCG-S) which improves the bioavailability significantly [74,75]. Previously, we reported that EGCG-S can be used as an anti-spore agent, as it inhibits germination of spores produced by Bacillus species [30]. In 2018, our study highlighted the anti-cariogenic property of EGCG-S as it was able to inhibit the growth and biofilm formation of S. mutans, an etiological agent of dental caries [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in this study, we have used a patented (US8076484B2) esterified derivative of EGCG, EGCG-Stearate (EGCG-S) which improves the bioavailability significantly [74,75]. Previously, we reported that EGCG-S can be used as an anti-spore agent, as it inhibits germination of spores produced by Bacillus species [30]. In 2018, our study highlighted the anti-cariogenic property of EGCG-S as it was able to inhibit the growth and biofilm formation of S. mutans, an etiological agent of dental caries [31].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG-S has been successfully shown to inhibit spores produced by Bacillus spp. and the growth of Streptococcus mutans (S. mutans) [30,31]. Additionally, EGCG-S was shown to improve the efficacy of antibiotics against various bacteria, thereby making it a potential synergistic anti-bacterial agent [32].…”
Section: Introductionmentioning
confidence: 99%
“…EGCG-S is a more stable derivative that can inhibit the production of bacteria secondary metabolites and thus induces endogenous oxidative stress and decreases biofilm formation [26]. Previous report also suggested that EGCG-S could damage the integrity of endospore coat [11]. The mechanisms of EGCG and EGCG-S may work synergistically with antibiotics to increase the susceptibility of antibiotic on antibiotic resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, EGCG is a water-soluble polyphenol oxidized and metabolized rapidly, which leads to the loss of potent antimicrobial abilities quickly [10]. To overcome the stability issue, the modified lipophilic polyphenols could be an effective agent as green tea polyphenols (GTPs) [11]. EGCG-stearate (EGCG-S), lipid soluble tea polyphenols (LTPs) that were prepared chemically and enzymatically, can significantly improve the bioavailability of GTPs [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…EGCG can be modified structurally to improve its lipophilicity, expand its application in lipophilic media, and enhance its cellular absorption in vivo. The fully acetylated derivative (EGCG-P) may act as a pro-drug, leading to higher bioavailability than EGCG itself [10]. Moreover, EGCG peracetated and EGCG fatty acid monoester derivatives may improve the anticancer and neuroprotective activity in an alkyl chain length-dependent manner [11].…”
mentioning
confidence: 99%